POSTPARTUM MOTHERS' BEHAVIOR IN CARE OF BABIES DURING NEW HABITS ADAPTATION IN HOSPITAL - Intan Kumalasari; Maksuk, Maksuk; Maliha Amin; Rahmad Aswin Juliansyah; Herawati Jaya (Perhimpunan Ahli Epidemiologi Indonesia, 2023)
Background: Indonesia is one of the countries affected by the Corona Virus Disease-19 (COVID-19) pandemic with a fluctuating number of confirmed events (new cases). One of the populations at risk for infection with the Covid-19 virus is postpartum mothers and newborns. More than 50% of infant deaths occur in the neonatal period, which is the first month of life. Babies who do not get adequate care can experience various infectious diseases through the umbilical cord, mouth, eyes and ears, both during breastfeeding, bathing the baby and daily care.Methods: This study is a descriptive study to describe the behavior of mothers in caring for newborns during the adaptation period of new habits after the COVID-19 pandemic at three regional hospitals, namely Prabumulih Hospital, Sekayu Hospital and Muara Enim Hospital in 2021. The population in this study was all postpartum mothers in July 2021, a sample of 96 postpartum mothers was taken by total sampling on 4-30 July 2021. Results: Univariate data analysis showed that 84,86% of mothers had good knowledge and 80,33% of postpartum mothers had a good attitude in care babies every day during the pandemic, especially always washing hands or using hand sanitizer when touching babies, reducing kissing babies and limiting the number of visits during the pandemic. Conclusion:Good knowledge leads to appropriate attitudes and actions in newborn care; It takes the participation of parents, families, and health workers to ensure the success of baby care in the new normal era.